Recreational use of wild edible mushrooms: mycological tourism in the world with an emphasis on Mexico - Jiménez-Ruiz, Andrea; Thomé-Ortiz, Humberto; Espinoza-Ortega, Angélica; Vizcarra Bordi, Ivonne (BOSQUE, 2017)
In several countries around the world, including Mexico, there is a trend towards sustainable forest management, which includes non-timber forest resources and new non-extractive activities such as tourism. One of the resources that has arisen high interest in this regard are wild edible mushrooms, whose economic and cultural importance gives them the ability to be diversified in a wide range of products and services. Among the forms of diversification of mycological resources is tourism based on wild edible mushrooms, which is a recreational activity based on knowledge, identification, gathering and tasting of mushrooms. This literature review deals with the antecedents related to the recreational use of wild edible mushrooms and their challenges at a global level, emphasizing, in the case of Mexico, an analytical perspective of the processes of productive restructuring of the forest spaces. Mycological tourism is shown as an ambivalent activity, which is placed between a mercantilist vision on mycological resources and a forest management tool, based on investment processes, regulation and spatial planning. For this reason, it is necessary to analyze the productive transformations of the forests to know the contribution of mycological tourism in the social transformation and the improvement of the living conditions of rural communities.